Analysis of The Influence of Islamic Income Ratio, Total Comprehensive Income, and NPF on Company Value with Profitability as Moderating Variables in Sharia Commercial Banks in Indonesia 2015-2019 - Saidah, Alfi; Bawono, Anton (IAIN Kudus, 2021)
Economic Value Added is an approach to assessing company performance, with the aim that the company's ability to create added value can influence investors who will invest in the company. The concept used in this approach is to pay attention to the funders in terms of expectations, interests, and degrees of justice as measured by weighted measures and the existing initial capital structure. The population in this study are Islamic Commercial Banks registered with the Financial Services Authority, totaling 11 Islamic Banks. In selecting the sample the method used is purposive sampling with the criteria that the author has set. The collection method in this study was carried out by looking at the annual financial statements of each Islamic bank registered with the Financial Services Authority. Based on the results of the moderation regression test, the results showed that IIR, TCI, NPF had no significant positive effect on EVA. ROA is not able to moderate IIR against EVA. ROA is not able to moderate TCI against EVA. ROA is not able to moderate NPF against EVA.